The Value of Catur Purusa Artha and Capital Structure as The Maximization Key of Financial Performance in LPD Buleleng District - Erik Trisnawati, Ni Luh De; Pasek, Gede Widiadnyana; Kartika, Riana Dewi (International Journal of Social Science and Business, 2019)
The purpose of this study is to examine the implementation of the value of Catur Purusa Arthaand capital structure, as the main foundation of business strategy to create maximum financial performance of LPD in Buleleng Regency. The study population was all active LPDs in Buleleng Regency. Sampling in this study using random sampling techniques to obtain as many as 60 observational data. The data analysis technique used in this research is the Component based SEM method, Partial Least Square (PLS). The results showed that the value of Catur Purusa Artha has a positive effect on Capital Structure and Financial Performance. Capital structure also has a positive effect on financial performance.